The Economics of Environmental Health: Bibliometric Insights into Cost-Benefit and Public Policy Approaches - Judijanto, Loso (West Science Nature and Technology, 2025)
Environmental health economics has emerged as a necessary interdisciplinary field of research that addresses the complex interaction among environment quality, public health, and economic policy. This study conducts a bibliometric analysis at the world level to map the intellectual landscape of the field, with a particular focus on cost-benefit analysis and public policy measures. Based on the Scopus database between 2000 and 2025 and VOSviewer for visual network analysis, the study identifies the top authors, institutions, countries, and research topics that have been prominent in the field. The findings of the research validate that "environmental health" is a overarching theme that connects clusters that deal with air pollution, healthcare policy, sustainable development, and environmental protection. United States, United Kingdom, China, and Germany are major contributors, and inter-disciplinary studies between public health, economics, and environmental sciences rise. Overlay and density visualizations throw into relief both old and emerging fields of research that hold significant lessons for future study and policy-making. The study adds to theory development in environmental health economics and provides practical guidance on aligning research priorities with global health and sustainability goals.